Kembar Mayang Dalam Tradisi Pernikahan Adat Jawa Masyarakat Dusun Krajan Desa Pesanggaran Kabupaten Banyuwangi (Kajian Bentuk, Fungsi Dan Makna) - Amelia Purwandini (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
The implementation of a ceremony in various regions throughout Indonesia must use the means that complement it, the means used in a ceremony must be different in one region from another, one example of a wedding ceremony in Java that uses twin mayang means, but these facilities are not well understood by the community, especially the younger generation today. The research entitled "Kembar Mayang in the Tradition of Javanese Traditional Marriage of the Krajan Hamlet Community of Pesanggaran Village, Banyuwangi Regency (Study of The Form of Function and Meaning)", has a formulation of the problem (1) How is the form and process of making KembarMayang in javanese traditional marriage ceremonies, (2) What is the function of the Kembar Mayang in the existing Javanese traditional marriage ceremony, and (3) What is the Philosophical meaning of the Kembar Mayang in the Javanese traditional marriage ceremony in Pesanggaran Village, Banyuwangi Regency. Based on the data analysis carried out, the results of the study were obtained in the form of: (1) From the aspect of the form of the process of making Kembar Mayang in the marriage tradition that uses the javanese traditional concept, including: the preparation stage starting from the meeting, the manufacturing stage which begins with the search and selection of materials until the redemption stage, and the final stage, namely the Panggih Manten procession. (2) From the aspect of function, among others: religious function, namely as a symbol of the embodiment of God and a symbol of the sanctity of the bride and groom. The two social functions are the interaction and cooperation of the makers of Kembar Mayang, Manten shamans, celebration owners and teenagers carrying Kembar Mayang based on sincerity that creates a peaceful, prosperous and harmonious life for the bride-to-be. The three aesthetic functions can be seen from the use of Kembar Mayang which can also be used as decorations to support wedding events. (3) From the aspect of meaning, among others: the meaning of ethics, the meaning of aesthetics, the meaning of divinity and the meaning of education.